Designing for the user experience of sociability in massively multiplayer online games - Christou, Georgios; Zaphiris, Panayiotis; Ang, Chee Siang; Law, Effie Lai-chong (My University, 2011)
The emergence of MMOGs has led to new ways of socializing with friends. Nowadays a good online game is also associated with the pleasure of socializing and interacting with other players. One cannot play a game solitarily in a meaningful sense without interacting with the other players. However, there are still no integrated ways of designing and evaluating the inherent sociability of MMOGs, nor are there methods or guidelines for evaluating social user experiences. Designers of MMOGs are often left to use their intuition and experience, many times leading to design failures. This SIG aims to further the understanding of the challenges relating to the design of the social interactions that users experience, and the way these manifest and are supported in Massively Multi-player Online Games (MMOGs). The goal is to examine the ways that sociability manifests in MMOGs and the way that design affects these manifestations.
Keywords: Design; Massively Multiplayer Online Games; Online Community; Social Networks; User/game experience